ACUTE PURULENT COMPLICATED PYELONEPHRITIS IN THE PRACTICE OF AN OBSTETRICIAN-GYNECOLOGIST (CLINICAL CASE) - Алена Васильевна Иванникова; Елена Валентиновна Гришкевич; Елена Николаевна Орлова; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес (Мать и дитя в Кузбассе)
Acute purulent pyelonephritis in pregnant women is characterized by severe kidney damage, often leading to intoxication, sepsis, obstructive pyelonephritis, emphysematous pyelonephritis, perinephric abscess, kidney transplant rejection and death. At the same time, the issues of prevention, diagnostics and differential diagnostics of the stages of the disease are far from being resolved. The reasons for this are the variety of subjective and objective manifestations of the disease associated with the inflammatory process in the upper urinary tract, reflecting both local manifestations and the systemic reaction of the body. The clinical and laboratory diagnostic methods used often do not allow either to establish or exclude the diagnosis.